Relationship Between Duration of Hypertension and Vision Problems in Hypertensive Patients: A Cross-Sectional Survey (Medical Forum Monthly, 2024)
Objective: To study the relationship between duration of hypertension and vision problems in individuals suffering from hypertension.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Medical Outpatient Department of Medicine, Shahida Islam Medical College and Hospital, Lodhran from April 2018 to September 2018.Materials and Methods: A cross-sectional survey was conducted on 307 patients of 18 or higher ages hospital with the utilization of convenient sampling technique Age, duration of hypertension and presence and type of vision problem in patients were evaluated with the help of a structured questionnaire developed specifically for the study. For inferential analysis chi-square test was employed. Potential confounding effect of age was controlled by means of stratification.Results: The outcome of the study predicted a significant positive association between longer duration of hypertension and presence of vision problems (p=0.004) where patients with longer duration of hypertension had higher prevalence of vision problems than those with shorter duration (66.7% vs. 48.1%) although after controlling for the potential confounding effect of age, this association no longer persisted in any of the two age groups (p>0.05 for both).Conclusion: The study results revealed a positive association between longer duration of hypertension and presence of vision problems, although not after controlling for the confounding effect of age. Moreover, no significant association between duration of hypertension and types of vision problems was observed in the study participants. Further evaluation of the study findings with more rigorous study designs and a larger sample size is recommended.